2016
DOI: 10.1038/onc.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

The Δ133p53 isoform and its mouse analogue Δ122p53 promote invasion and metastasis involving pro-inflammatory molecules interleukin-6 and CCL2

Abstract: A number of naturally occurring isoforms of the tumour suppressor protein p53 have been discovered, which appear to have differing roles in tumour prevention or promotion. We are investigating the tumour-promoting activities of the Δ133p53 isoform using our mouse model of Δ133p53 (Δ122p53). Here, we report that tumours from Δ122p53 homozygous mice show evidence of invasion and metastasis and that Δ122p53 promotes migration though a 3-dimensional collagen matrix. We also show that Δ122p53 and Δ133p53 promote ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 31 publications
7
48
0
Order By: Relevance
“…33 Very recently, Roth et al showed that the mouse-specific isoform Δ122p53, similar to the human Δ133p53 isoform, which is overexpressed in melanoma, 34 promoted invasion in an IL-6- and CCL2-dependent manner. 35 We therefore tested whether p53 could specifically regulate invasion in a Tspan8-dependent manner. p53 silencing was shown to increase the invasiveness of T1C3 melanoma cells in Boyden chambers (Figure 4a), whereas p53 stabilization by nutlin-3 treatment is sufficient to decrease invasive capacities (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…33 Very recently, Roth et al showed that the mouse-specific isoform Δ122p53, similar to the human Δ133p53 isoform, which is overexpressed in melanoma, 34 promoted invasion in an IL-6- and CCL2-dependent manner. 35 We therefore tested whether p53 could specifically regulate invasion in a Tspan8-dependent manner. p53 silencing was shown to increase the invasiveness of T1C3 melanoma cells in Boyden chambers (Figure 4a), whereas p53 stabilization by nutlin-3 treatment is sufficient to decrease invasive capacities (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…D133p53a has been shown to stimulate proliferation (6) and angiogenesis of tumor cells (6) and D133p53b promotes stem cell differentiation by upregulating pluripotency factors such as SOX2, OCT3/4, and NANOG (24). A mouse model of D133p53 designated D122p53 was shown to promote hyperproliferation, tumorigenesis, and inflammation (9) and overexpression of D122p53 promoted cell migration, invasion through three-dimensional (3D) matrices (16), and upregulation of metastasis-associated proteins (14). Finally, recent data from the D122p53 mouse has shown that there is also cooperativity as D122p53 enhanced the survival of p53-mutant mice (25) and full-length p53 increased the ability of D122p53 to promote cell migration (16).…”
Section: Introductionmentioning
confidence: 99%
“…A mouse model of D133p53 designated D122p53 was shown to promote hyperproliferation, tumorigenesis, and inflammation (9) and overexpression of D122p53 promoted cell migration, invasion through three-dimensional (3D) matrices (16), and upregulation of metastasis-associated proteins (14). Finally, recent data from the D122p53 mouse has shown that there is also cooperativity as D122p53 enhanced the survival of p53-mutant mice (25) and full-length p53 increased the ability of D122p53 to promote cell migration (16). This is consistent with the isoforms functioning in a complex network to determine cell fate outcomes (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D133p53b also prevents cancer cells from undergoing apoptosis in a RhoB-dependent manner (40). It has been suggested that the D133p53 isoform and its mouse analog D122p53 promote invasion and metastasis in a manner similar to gain-offunction of mutant p53 proteins (41). Therefore, it is important to understand the physicochemical properties of D133p53b compared with p53 protein with normal DBD.…”
mentioning
confidence: 99%